Application Of Contingency Theory Of Accounting Information To The Uae Banking Sector - A. Alrawi, Hikmat; Thomas, Suja Sarah (Asian Academy of Management (AAM), 2007)
Although extensively studied in the last two decades, contingency theory has been given relatively little consideration in terms of the factors that influence the accounting information systems. Few organizations appear to have systematic processes in place for managing the evolution of their measurement systems and few researchers appear to have explored two of the main questions: What are the requirements of accounting information in UAE banks? And, how efficient is the accounting systems in UAE banks? The paper addresses these questions by providing empirical evidence of management accounting information contingencies based on a sample of banks in the UAE.